2013
DOI: 10.1097/opx.0b013e318296ac4d
|View full text |Cite
|
Sign up to set email alerts
|

Factors Accounting for the 4-Year Change in Acuity in Patients Between 50 and 80 Years

Abstract: Purpose It is well known acuity slowly decreases in later decades of life. We wish to determine the extent 4 year longitudinal acuity changes can be accounted for by changes in optical quality, or combination of optical quality metrics and age between 50 and 80. Methods High contrast logMAR acuity, 35 image quality metrics, 4 intraocular scatter metrics, and 4 Lens Opacification Classification System-III metrics and entry age were measured on one eye of each of 148 subjects. Acuity change between baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Our findings might become more useful if the ability to predict visual deterioration in the elderly is substantiated 32. This study, given its large cohort, further establishes this association and discloses its relevance at an earlier point than previously thought.…”
Section: Discussionsupporting
confidence: 70%
“…Our findings might become more useful if the ability to predict visual deterioration in the elderly is substantiated 32. This study, given its large cohort, further establishes this association and discloses its relevance at an earlier point than previously thought.…”
Section: Discussionsupporting
confidence: 70%
“…Hence, the best image quality metric accounted for 2.6%, 15.1%, 27.6% and 40% of the variance taking into account various types of logMAR acuity. Koenig et al . studied the effect of various metrics on changes in logMAR and reported r 2 values in the range 3–21%.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the best image quality metric accounted for 2.6%, 15.1%, 27.6% and 40% of the variance taking into account various types of logMAR acuity. Koenig et al 20 studied the effect of various metrics on changes in logMAR and reported r 2 values in the range 3-21%. One of the more extreme examples was reported by Nomura et al, 21 intraocular pressure (IOP) in a large Japanese population was inversely correlated with age in men (r = À0.14, p < 0.001).…”
Section: A Significant 'R' Does Not Always Indicate a Meaningful Relamentioning
confidence: 99%
“…As a result, some studies report a significant value of r but very low values of r 2 . Koenig et al . ( N = 148), for example, studied the effect of various metrics on changes in logMAR and reported r 2 values in the range 3–21%.…”
mentioning
confidence: 99%
“…As a result, some studies report a significant value of r but very low values of r 2 . Koenig et al 6 (N = 148), for example, studied the effect of various metrics on changes in logMAR and reported r 2 values in the range 3-21%. Moreover, Nomura et al 1 studied intraocular pressure (IOP) in a large Japanese population (N = 1317) and found that IOP was inversely correlated with age in men (r = À0.14, p < 0.001).…”
mentioning
confidence: 99%